Pre-Wisconsin stratigraphy and paleoclimates off Atlantic Canada, and its bearing on glaciation in Québec - Alam, M.; Piper, D. (Géographie physique et Quaternaire, 1977)
Cores from tops of seamounts close to the continental shelf west of the Grand Banks contain sequences of alternating clays (representing glacials) and foram nanno ooze (deposited in warmer periods), back to the Pliocene. Although sedimentation in the cores is controlled primarily by glacial conditions on the Grand Banks and Laurentian Channel, glacial history further inland can be inferred. The Wisconsin sequence shows two cool interstadials and one rather warmer one, correlable with the Plum Point, Port Talbot and St. Pierre Interstadials. Clay sedimentation during Wisconsin glacial stages was minor, suggesting glaciers did not extend to the shelf edge. In the late lllinoian, there was a major influx of red sediments, indicating significant erosion of the Gulf of St. Lawrence and Laurentian Channel. Glaciation was more extensive than during the Wisconsin. Two lllinoian interstadials, with temperatures between those of the Plum Point and St. Pierre interstadials are recognised. Early lllinoian glaciation was the most severe yet recognised in the cores. Sedimentation appears to have been controlled by the advance of a Newfoundland — Labrador — E. Québec ice sheet across the Grand Banks.